Multi-Physics Simulation of 6/4 Switched Reluctance Motor by Finite Element Method - Renata R. C. Reis; Marcio L. M. Kimpara; João O. P. Pinto; Babak Fahimi (Eletrônica de Potência)
The switched reluctance motor (SRM) performance can be improved by either drive control and/or machine design. However, the drive control may be more complex and expensive depending on the SRM design, whereas a favorable SRM design may result in simpler and cheaper drive control system. In order to evaluate the SRM performance before designing the control/drive system, it is important carrying out a multi-physics simulation of the machine, in such way that if electromagnetics, structural and thermal performance do not cope with the requirements for simpler control/drive system, the SRM can be redesigned until reach a feasible goal. This paper presents a comprehensive simulation analysis of a 6/4 three-phase SRM using the finite element method as evaluation approach for future use in optimization design techniques. First, the main geometrical parameters of the motor were calculated and then static and dynamic simulations were conducted to analyze the motor electromagnetic performance. Afterwards, the natural frequencies and vibration modes were found through modal analysis. Finally, the thermal analysis was accomplished to investigate the internal temperature rise due to the copper losses. The analysis has been performed in ANSYS package, providing an insightful guidance for the near optimum motor designing stage.